Tantangan Pendidikan Islam di Era Global: Strategi Integratif Menuju Pendidikan yang Adaptif dan Transformatif - Jelly Raisa Zahra; Rani Sagita Permata Sari; Arda Zul Kaesyh; Hanggia Sahfitri; Darul Ilmi (SURAU : Journal of Islamic Education, 2026)
This article aims to analyze the challenges of Islamic education in the global era and formulate an integrative strategy to ensure that it remains adaptive, value-oriented, and transformative. The study employed a qualitative approach using a library research method based on a review of national and international literature, including journal articles, books, institutional reports, and empirical data on digital transformation, teacher professionalism, curriculum reform, character education, and the epistemology of Islamic education. The data were analyzed using thematic content analysis through theme identification and strategic synthesis. The findings indicate that the challenges of Islamic education stem not only from globalization and digital culture but also from internal issues, including the dichotomy between religious and general sciences, a certification-oriented educational paradigm, limited digital competence among educators, unequal access to technology, and the suboptimal internalization of Qur’anic character values. The novelty of this study lies in the formulation of a transformative-integrative framework for Islamic education that integrates digital literacy, the ethical use of technology, participatory curriculum development, teacher professionalism, knowledge integration, and collaboration among schools, families, and communities. This article offers a strategic synthesis for developing Islamic education that is intellectually competitive, spiritually grounded, and responsive to the global challenges of the twenty-first century.